First record of the Mediterranean parrotfish, Sparisoma cretense in Ria Formosa (south Portugal) - Abecasis, D. (2017)
Several juvenile specimens of Sparisoma cretense, a previously unrecorded species, were caught using beach seining in Ria Formosa.The hypothesis that these occurrences are related with climatic changes is discussed.